Vaccine hesitancy in case of under-5 vaccination in slums of Burdwan Municipality, West Bengal: A cross-sectional study - Nayak, Sayantani; Das, Dilip Kumar; Thakur, Rupali; Banerjee, Niladri (Asian Journal of Medical Sciences, 2022)
Background: There are multiple reasons for which a considerable proportion of the population remains unvaccinated, including vaccine hesitancy. Identifying the reasons behind vaccine hesitancy, especially in marginalized population, is essential. Aims and Objectives: The aims of the study were to estimate the magnitude and determinants of vaccine hesitancy related to under-5 vaccination in slums of Burdwan Municipality, West Bengal. Materials and Methods: A community-based descriptive study with cross-sectional design was conducted between September 2020 and January 2021 among 135 study subjects (under-5 children) selected by multistage random sampling. Data were collected by interviewing the primary caregivers of selected children using a predesigned schedule including vaccine hesitancy survey questionnaire by Strategic Advisory Group of Experts. Data analysis was done using SPSS v.20. Results: Vaccine hesitancy was found in case of 11.9% of the study subjects. Refusal was seen in 2.2%, only in case of birth doses, whereas hesitancy due to delay was seen in 9.7% in case of MR, JE, DPT, and OPV boosters. Stated reasons for hesitancy were – “vaccine was not needed” (47.4%), “fear of needles” (31.5%), and “not able to leave other work at home” (21.1%). Caregivers of 17% of the study subjects faced difficulty from getting their child immunized mainly due to timing of the clinic and lockdown. The presence of vaccine hesitancy was not associated with sociodemographic characteristics of the child or of the caregivers. Conclusion: Vaccine hesitancy was found to be low in the study area, it was mainly to birth doses and mostly due to lack of awareness among caregivers.